The link between optic neuritis and multiple sclerosis. Literature review - Kubiliūtė , A.; Liutkevičienė , R. (Neurologijos seminarai, 2021)
Optic neuritis and multiple sclerosis are connected via processes of demyelination and neurodegeneration in the central nervous system. Immuno-modulated myelin sheathing and axonal loss causing irreversible neurological dysfunction can be found in both pathologies. Patients who experience these conditions are usually young adults, therefore early diagnosis and control of the disease may benefit in preserving their neurological function and quality of life. The first attack of multiple sclerosis often presents as optic neuritis which is important to distinguish based on appropriate clinical signs and evaluation of diagnostic features. Some diagnostic methods may not only help to understand the cause of vision loss, but also provide predictive value for the development of multiple sclerosis in the future. Unfortunately, no effective treatment to slow the progression of the disease has been approved yet. Intravenous and oral corticosteroids, intravenous immunoglobulin, and therapeutic plasmapheresis are used to manage acute episodes of optic neuritis; however, the effectiveness of such treatment is also debatable. Thereby, new substances are being researched recently to evaluate their significance in the processes of remyelination and neuroprotection. Some aspects of epidemiology, etiology, pathogenesis, clinical signs, possibilities of diagnosis and treatment of optic neuritis together with the evaluation of the risk of multiple sclerosis development are discussed in this article.